تاثير الصحافة الوطنية على تلبية انشغالات المواطنين - طيفوري عيسى; سائحي سويح; د/ شوشة حرزالله (جامعة عمار ثليجي الاغواط, 2025)
في عصر الثورة الرقمية وتطور وسائل التواصل الاجتماعي، لم تعد الصحافة مقتصرة على المؤسسات الإعلامية الكبرى أو الصحفيين المحترفين، بل أصبح بإمكان كل فرد يمتلك هاتفًا ذكيًا واتصالًا بالإنترنت أن يكون مراسلًا وشاهدًا على الأحداث من حوله. من هنا نشأت ظاهرة "صحافة المواطن"، التي أتاحت للمواطن العادي الإسهام في تغطية الأحداث اليومية، ونقل واقع الحياة كما يراه ويعيشه. ومن أبرز المجالات التي برز فيها هذا الدور، ما يتعلق بإشغالات المواطن، كقضايا الطرق، والمرافق العامة، والتعديات، والخدمات البلدية، وغيرها من المشكلات التي تمس حياة الناس اليومية.تلعب صحافة المواطن دورًا محوريًا في تسليط الضوء على هذه الإشغالات، حيث تسهم في نقل صوت المواطن وهمومه إلى الجهات المختصة بشكل فوري. كما أنها تُعد وسيلة رقابية شعبية، تحفز على الاستجابة السريعة ومعالجة القضايا التي قد تغيب عن أعين الإعلام التقليدي أو الجهات الرسمية. لذا، فإن صحافة المواطن لم تعد مجرد وسيلة للتعبير، بل أصبحت أداة فاعلة في تحقيق الشفافية والمساءلة، والمساهمة في تحسين جودة الحياة والخدمات العامة. ولقد حاولنا من خلال هذه الدراسة التركيز على إبراز مساهمة صحافة المواطنة في انشغالات المواطنين من خلال دراسة قمنا بها على عينة من صحفيي ولاية –الأغواط-، وانطلقت دراستنا من إشكالية تمثلت في:  كيف تساهم صحافة المواطن في انشغالات المواطنين؟ الكلمات المفتاحية: صحافة المواطنة، المواطن. In the era of the digital revolution and the development of social media, journalism is no longer limited to major media organizations or professional journalists. Rather, anyone with a smartphone and an internet connection can become a reporter and witness to the events around them. Hence, the phenomenon of "citizen journalism" emerged, allowing ordinary citizens to contribute to covering daily events and conveying the reality of life as they see and experience it. Among the most prominent areas in which this role has emerged are those related to citizen concerns, such as road issues, public facilities, encroachments, municipal services, and other problems that affect people's daily lives. Citizen journalism plays a pivotal role in shedding light on these concerns, contributing to the immediate transmission of citizens' voices and concerns to the relevant authorities. It also serves as a popular oversight tool, encouraging rapid responses and addressing issues that may otherwise be overlooked by traditional media or official bodies. Therefore, citizen journalism is no longer merely a means of expression; it has become an effective tool for achieving transparency and accountability, and contributing to improving the quality of life and public services. Through this study, we sought to highlight the contribution of citizen journalism to citizens' concerns through a study we conducted on a sample of journalists in the state of LAGHOUAT. Our study began with the following question:  How does citizen journalism contribute to citizens' concerns? Keywords: Citizen Journalism, Citizen.
دراسة على عينة من الصحفيين المواطنين بولاية الاغواط